Political reform in Japan : leadership looming large - Gaunder, Alisa, 1970- (Routledge contemporary Japan series ;, 2007)
"Political Reform in Japan argues that the quality of political leadership is the crucial determinant of whether politicians pass or reject policies such as electoral system and campaign finance reforms that could harm their future electoral chances. Alisa Gaunder reveals that while scandal is necessary to open windows of opportunity for reform, scandal itself does not produce reform. A leader with a certain set of resources and personal attributes is also needed, both to persuade self-interested politicians to support reform and to keep this support mobilized."--BOOK JACKET.